Ataluren delays loss of ambulation and respiratory decline in nonsense mutation Duchenne muscular dystrophy patients - McDonald, Craig M; Muntoni, Francesco; Penematsa, Vinay; Jiang, Joel; Kristensen, Allan; Bibbiani, Francesco; Goodwin, Elizabeth; Gordish-Dressman, Heather; Morgenroth, Lauren; Werner, Christian; Li, James; Able, Richard; et al. (Journal of comparative effectiveness research, 2022)
We investigated the effect of ataluren plus standard of care (SoC) on age at loss of ambulation (LoA) and respiratory decline in patients with nonsense mutation Duchenne muscular dystrophy (nmDMD) versus patients with DMD on SoC alone. Study 019 was a long-term Phase III study of ataluren safety in nmDMD patients with a history of ataluren exposure. Propensity score matching identified Study 019 and CINRG DNHS patients similar in disease progression predictors. Ataluren plus SoC was associated with a 2.2-year delay in age at LoA (p = 0.0006), and a 3.0-year delay in decline of predicted forced vital capacity to <60% in nonambulatory patients (p = 0.0004), versus SoC. Ataluren plus SoC delays disease progression and benefits ambulatory and nonambulatory patients with nmDMD. : .